Discourse on Land in Kathmandu - Maharjan, Mahesh Raj (Dhaulagiri Journal of Sociology and Anthropology, 2022)
With increasing migration, commodification of land, and urbanization in Kathmandu, there is growing interaction and antagonism between local landowners and groups who wish to own land, which has generated a discourse about land. This paper considers perceptions, beliefs, practices, and policies about land as discourse on land. Such discourse included meanings and uses of land. On discourse about landownership, land seekers think that Newars do not need the land that they are historically owning, and land brokers (dalāls) are suggesting landowners to sell land and build houses or live off on the interest of the money by depositing it in the bank. Dalāls act not only as intermediaries between owners and buyers in the land market but as amplifiers and communicators, and often as creators, of discourse. The physical and socio-economic environment of Kathmandu is changing in such a way that landowners are unable to hold, or hold for long, their land, and they are becoming increasingly influenced by the discourse that land is a high-value commodity that should be sold. Such discourse can be explained by the political economic theory that considers the city as a growth machine that commodifies space for private profit-making and capital accumulation.